Association Between Endometriosis and Hypercholesterolemia or Hypertension. Issue 1 (July 2017) - Mu, Fan; Rich-Edwards, Janet; Rimm, Eric B.; Spiegelman, Donna; Forman, John P.; Missmer, Stacey A.
Abstract : An altered hormonal or chronic systemic inflammatory milieu characterizing endometriosis may result in a higher risk of hypercholesterolemia and hypertension. Conversely, elevated low-density lipoprotein in hypercholesterolemia and chronic systemic inflammation resulting from hypertension may increase the risk of endometriosis. We assessed the association of laparoscopically confirmed endometriosis with hypercholesterolemia and hypertension in a large prospective cohort study. In 1989, 116 430 registered female nurses aged 25 to 42 completed the baseline questionnaire and were followed for 20 years. Multivariable Cox proportional hazards models were applied. In 1989, there were 4244 women with laparoscopically confirmed endometriosis and 91 554 women without. After adjusting for demographic, anthropometric, family history, reproductive, dietary, and lifestyle risk factors prospectively, comparing women with laparoscopically confirmed endometriosis to women without, the relative risks were 1.25 (95% confidence interval, 1.21–1.30) for development of hypercholesterolemia and 1.14 (95% confidence interval, 1.09–1.18) for hypertension. Conversely, the relative risks of developing laparoscopically confirmed endometriosis were 1.22 (95% confidence interval, 1.15–1.31) comparing women with hypercholesterolemia to women without and 1.29 (95% confidence interval, 1.18–1.41) comparing women with hypertension to women without. The strength of associations of laparoscopically confirmed endometriosis with hypercholesterolemia or hypertension was strongest among women aged ⩽40 and weakened as age increased ( P values for interaction <0.001). We observed that ≈45% of the associations between endometriosis and hypercholesterolemia and hypertension could be accounted for by treatment factors after endometriosis diagnosis, including greater frequency of hysterectomy/oophorectomy and earlier age for this surgery. In this large cohort study, laparoscopically confirmed endometriosis was prospectively associated with increased risk of hypercholesterolemia and hypertension. Conversely, hypercholesterolemia and hypertension were prospectively associated with higher risk of laparoscopically confirmed endometriosis.